Wegener’s Granulomatosis Presenting With an Isolated Paranasal Sinus Involvement in a Child - Ghaniya DAAR; Ali Bülent CENGİZ and Ateş KARA and Rezan TOPALOĞLU and Ömer Taşkın YÜCEL and İsmail DURSUN4 (Archives of Rheumatology, 2014)
Wegener’s granulomatosis which is rarely seen in children is an idiopathic necrotizing granulomatous vasculitis, affecting primarily paranasal sinuses, nasopharynx, lungs, kidneys and joints. In this article, we report a very rare case of eight-year-old boy presenting with Wegener’s granulomatosis of paranasal sinuses without lung, kidney and any other organ involvement. We discuss the diagnosis, treatment and the differential diagnosis of paranasal sinus involvement in Wegener’s granulomatosis in the light of literature data.